2003
DOI: 10.1034/j.1399-0012.2003.00017.x
|View full text |Cite
|
Sign up to set email alerts
|

Steroid‐free immunosuppression during and after liver transplantation – a 3‐yr follow‐up report

Abstract: Steroids are not necessary in more than 50% of liver transplantations. Steroids were transiently needed to treat acute rejection in 23.5% liver transplantations and for toxicity of calcineurin inhibitors or azathioprine or other reason in 28%. Of the patients who received steroids, the majority (70%) was eventually taken off steroids. This prospective single-center pilot study shows that liver transplantation without steroids is feasible and yields no penalty in terms of acute and chronic rejection, immune gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
1
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 20 publications
2
34
1
1
Order By: Relevance
“…Early steroid-withdrawal regimens do not increase the rejection rate [7][8][9][10][11] . Padbury [12] has reported that, when steroids were withdrawn safely in 140/197 patients (71%), the acute and chronic rejection rate was 4.5 and 3.9%, respectively, and this was similar to the reported rates with steroid-containing regimens.…”
Section: Discussionmentioning
confidence: 99%
“…Early steroid-withdrawal regimens do not increase the rejection rate [7][8][9][10][11] . Padbury [12] has reported that, when steroids were withdrawn safely in 140/197 patients (71%), the acute and chronic rejection rate was 4.5 and 3.9%, respectively, and this was similar to the reported rates with steroid-containing regimens.…”
Section: Discussionmentioning
confidence: 99%
“…administration on anastomotic leaks in colorectal surgery was examined using the PETO odds ratio method as anastomotic leaks were anticipated to be rare events. 21 Medians were converted to means using the technique described by Hozo et al 31 Forest plots were then constructed with P < 0.05 considered statistically significant. Statistical heterogeneity was evaluated using I 2 statistics and a χ 2 test for heterogeneity was performed, with P < 0.1 regarded as statistically significant.…”
Section: Data Abstractionmentioning
confidence: 99%
“…20 GCs have also been used for immunosuppression in liver transplantation and may improve postoperative outcomes. 13,[21][22][23] However, their safety and efficacy has not been established in major elective abdominal surgery with concerns regarding potential increases in infectious complications. 10 Moreover, GCs cause hyperglycaemia which is now known to be associated with an exaggerated catabolic response and increased complications.…”
mentioning
confidence: 99%
“…Moreover, chronic steroid use likely is not necessary for other abdominal organ transplants either. Reports of steroid-free immunosuppression have been published for pediatric recipients of kidney [44] and liver [45] transplants, adult recipients of liver allografts [46], and recipients of pancreas transplants [47,48], further supporting this position.…”
Section: Future Strategies In Immunosuppressionmentioning
confidence: 94%